T-bet+ILC3 in peripheral blood is increased in the ankylosing spondylitis with high disease activity - Yang Liu; Yi Shen; Hongbai Ding; Dongyi He; Peng Cheng; Xinyao Wu; Zheng Xiang; Lei Shen; Yanqin Bian; Qi Zhu (Heliyon)
Objective: Ankylosing spondylitis (AS) is a chronic autoimmune disease characterized by systemic inflammation, often resulting in fusion of the spine and peripheral joints. This study aimed to investigate the role of innate lymphoid cells (ILCs) in AS patients with high disease activity. Methods: Blood samples were collected from healthy controls and AS patients categorized by high or low disease activity. Systemic inflammation was quantified through C-reactive protein (CRP) levels and erythrocyte sedimentation rate (ESR), alongside disease activity scores such as Ankylosing Spondylitis Disease Activity Score(ASDAS) and Bath Ankylosing Spondylitis Disease Activity Index(BASDAI). The levels of different ILC subsets and the expression of T-box transcription factor 21 (T-bet) and retinoic-acid-receptor-related orphan receptor gamma (RORγt) in peripheral blood were analyzed via flow cytometry. Additionally, 24 cytokines in plasma were measured using a Luminex liquid suspension chip. Results: The proportion of total ILCs and the distribution of ILC subsets in peripheral blood varied with AS disease activity scores. Specifically, the frequencies of total ILCs and ILC3s were significantly elevated in AS patients with high disease activity (AS-HA). The frequency and absolute number of ILC3s showed a positively correlation with disease severity scores. Furthermore, T-bet+ILC3s were significantly increased in the AS-HA group. Plasma levels of IL-17A and IFN-γ were positively correlated with the frequency of circulating-ILC3 in AS patients. Conclusions: These findings highlight the critical role of T-bet+ILC3s in the inflammatory process of AS, suggesting their potential as a therapeutic target for managing AS disease.